Managerial Transformation at Sea: Strategies to Enhance Performance, Motivation and Crew Safety - Aziz, Azmal; Mulyanti, Rita Yuni; Soma, Abdul Mukti (International Journal of Multidisciplinary Research of Higher Education, 2025)
Work safety and crew performance are very important focus areas in the high-risk maritime industry, as exemplified by shipping companies. This study aims to analyze the impact of leadership and managerial competence on crew motivation and performance, as well as their influence on work safety. This study uses quantitative methods with a causal design used to examine cause-and-effect relationships among variables, including leadership, managerial competence, work motivation, crew performance, and work safety. Data were collected through a survey using a Likert-scale questionnaire with five response levels. The respondents were crew members working for a shipping company. Additional data collection techniques included field observations and literature review to complement the theoretical insights. Data analysis was conducted using Structural Equation Modeling with SmartPLS software. The findings indicate that transformational leadership and managerial competence significantly influence work motivation and crew performance. Moreover, work motivation serves as a mediating variable, strengthening the relationships between leadership and performance, as well as managerial competence and occupational safety. This study emphasizes the crucial role of effective leadership in workplace safety within the maritime industry. Its implications suggest that companies should enhance competency-based training and leadership strategies to optimize crew performance and ensure sustainable workplace safety.